Polymer Brush Modified Electrode with Switchable Selectivity Triggered by pH Changes Enhanced by Gold Nanoparticles - Sempionatto, Juliane R. [UNESP]; Pedrosa, Valber A. [UNESP]; Pal, M. (Destech Publications, Inc, 2014)
In this work a pH sensor was build up with smart material based on polymer brush and gold nanoparticles. The modified electrode functionalized with a polymer brush Polyacrylic Acid (PAA) tethered to the surface and covered with gold nanoparticle (ITO/PAA/Au) demonstrated switchable interfacial properties discriminating different pHs. The switchable electrochemical and plasmonic process was characterized by differential pulse voltammetry (DPV), Faradaic impedance spectroscopy (EIS), cyclic voltammetry (CV) and Localized Surface Plasmon Resonance (LSPR).
Keywords: Polyacrylic Acid (PAA); LSPR; polymer brush; pH sensor